KEEFEKTIVAN METODE LEARNING STARTS WITH A QUESTION PADA PEMBELAJARAN GEOMETRI - Pradana, Lingga Nico (Profesi Pendidikan Dasar, 2016)
This purpose of the research was to determine the effectiveness of learning start with a questionmethods on geometry learning. The effectiveness of these methods would be compared withpresentation method. The method of this research was quasi experimental method with 2x1factorial design. The population in this study was the third semester students at PGSD IKIPPGRI MADIUN while the sample was 3G as an experimental class and 3C as the control class.The sampling technique used was cluster random sampling. Methods of data collection in thisstudy was test method and divided into two: pre-test and post-test. Data analysis techniquesused in this study is a t-test with two independent samples. The results of this study were learningstarts with a question method was more effective than presentation method.